The Importance of Clinical Psychologist in the Process of Divorce - MUSTAFARAJ, Jonida (European Journal of Multidisciplinary Studies, 2017)
The Family Code in Section 6, 155 is foreseen to include clinical psychologist in the process of divorce in court in cases where the parties are in conflict, when it is claimed elements of physical and psychological violence perpetrated by one or both parties towards each - other or child. The aim of this study was to reveal the importance of the involvement of a clinical psychologist in the process of divorce. So study aims to highlight the necessity of the presence of a clinical psychologist in the process of divorce within the framework of the general principles of the Family Code as long as it guarantees the right to be heard by the parties involved they also guarantee the right presence of a psychologist in the process. The study was conducted on the basis of qualitative methods which deal mostly with history and stories and include subjective meanings, feelings, thoughts and beliefs. The approach used in the study is the epistemological interpretation. Qualitative data were collected on an examination of 60 cases of divorces filed in the District Court of Elbasan in the period January - May 2016. This study emphasized the importance and necessity of a clinical psychologist as an expert in the process of divorce as the expertise provided is a guarantee of the process and respect for the rights of the child in the first place and for the parties involved in the process.